The House of New Beginnings - Diamond, Lucy, 1970- (Pan Books, 2017)
From the Sunday Times bestselling author of The Secrets of Happiness and Summer at Shell Cottage, this is a story about love, loss and starting over.
Keywords: England--Brighton -- Roommates -- Women cooks